Family Systems, Counselling, and School Problems - Ryan, Bruce A.; Barham, Richard M. (Canadian Journal of Counselling and Psychotherapy, 2011)
In recent years numerous papers have appeared which encourage school counsellors and school psychologists to appreciate the special role families might play in school problems experienced by children. Specifically, it is suggested that a proportion of children's school problems might be serving a functional role in the family system and that family members may act in ways to maintain those problems for the sake of family stability. The clinical and empirical evidence supporting such a view is examined and some implications for the school counsellor are discussed.